Analisis pengendalian internal aktiva tetap sebagai tindak pencegahan penyimpangan pada PT Manado Teknik Mandiri - Paput, Clauditha Maria Imaculata; Gerungai, Natalia Y. T. (Yayasan Widyantara Nawasena Raharja, 2024)
Internal control is a system designed to provide protection and security for various elements within the company so that with effective internal control, the risk of fraud can be prevented. With good internal control, companies can identify and address risks, including fraud risks, before they occur and reduce their impact. The purpose of this study is to find out how the implementation of internal control and to find out whether the internal control applied is effective in preventing irregularities, especially misuse of fixed assets at PT Manado Teknik Mandiri. The type of research used is descriptive qualitative. The results of research obtained at PT Manado Teknik Mandiri show that the implementation of internal control of fixed assets based on the COSO framework has not been fully implemented. And the internal controls carried out by the company have been effective in preventing irregularities. However, not all components have effectively contributed.